Constitutional guarantees and the distribution of power and wealth - Jürgen Backhaus (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1976)
Given the constitution of a particular society, this constitution needs to be adopted to changing social realities. This may be achieved by either interpretation or amendment. This paper seeks to provide an analysis of the Process of the Interpretation of the Constitution (PIC), by which constitutional norms are not only applied and adopted to changing circumstances but essentially changed in content. The model of a System of Interpretation of the Constitution (SIC) is advanced in order to specify the conditions, under which constitutional change by interpretation will take place, and to indicate the directions, in which the authentic interpretation of the constitution will shift. SIC is described by 15 assumptions, with the distinction being made between different scenarios of constitutional change by interpretation (see Propositions I - III). The relevance of this paper lies in the attempt to demonstrate the social consequences of using SIC as a mechanism to resolve social and political conflicts - rather than employing conventional public choice procedures.
Keywords: 330